The Interplay between International Trade and Technological Change and the wage inequality in the OECD Countries - Nikolina Stojanovska; Ludo Cuyvers (FIW - Research Centre International Economics, 2010)
We estimate the impact of international trade and of trade-induced technological change on the wage inequality in the OECD countries, by estimating a two-stage mandated-wage regression. From our estimation we find no evidence on the Stolper-Samuelson effect of trade with the developing and newly industrialized countries. On the other hand, the evidenced technological change from technological competition did not have a strong effect on the increase of the wage differential between the different types of labour in the analyzed sample of OECD countries, which would have indicated that the bias of the technological change towards the skilled-intensive sectors is determined by trade in innovation-intensive goods.
Keywords: F1; O3; 330; price competition; technological competition; wage inequality